CELF1 promotes aerobic glycolysis and an aggressive phenotype in ER-positive breast cancer via GLUT1 regulation - Li, Jinyu; Wang, Ning; Bi, Jianlei; Guo, Meihua; Xu, Bingbing; Huang, Gena (Frontiers in Genetics, 2025)
IntroductionRNA-binding proteins (RBPs) shape post-transcriptional programs in cancer, yet subtype-specific roles in breast cancer remain unclear. We evaluated whether CUGBP Elav-like family member 1 (CELF1), an RBPs with prognostic relevance in luminal A (ER-positive) breast cancer, drives malignant phenotypes via glycolytic reprogramming through glucose transporter 1 (GLUT1).MethodsWe surveyed 1,337 RBPs across TCGA to identify luminal A prognosis-related candidates using Cox models and random-forest ranking, then validated CELF1 biologically. Functional assays combined CELF1 knockdown in ER-positive cells (MCF7, T47D) and overexpression in HER2-positive cells (SKBR3, HCC1954), RNA-seq with differential expression and GSEA, qPCR,western blot, migration, colony assays, IHC in clinical tissues, and a nude-mouse xenograft with the GLUT1 inhibitor BAY-876.ResultsCox and random-forest analyses prioritized CELF1 among prognosis-related RBPs in luminal A tumors; high CELF1 associated with poorer survival and was overexpressed in breast cancer versus normal tissue. CELF1 modulation bidirectionally altered glycolytic programs and malignant traits: CELF1 loss reduced proliferation, colony formation, migration, and xenograft growth, whereas overexpression enhanced these phenotypes. RNA-seq and enrichment analyses highlighted suppression of glycolysis pathways upon CELF1 loss; GLUT1 (SLC2A1), HK2, and G6PD were consistently downregulated at mRNA and protein levels after CELF1 knockdown and upregulated with CELF1 overexpression. In vivo, combining CELF1 knockout with BAY-876 further curtailed tumor growth and proliferation markers.ConclusionCELF1 promotes aerobic glycolysis and aggressive behavior in ER-positive breast cancer, at least partly by regulating GLUT1. These findings reveal RBP-driven metabolic reprogramming in luminal A disease and nominate the CELF1–GLUT1 axis as a potential therapeutic vulnerability.